2001
DOI: 10.1103/physreve.63.061501
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-liquid equilibrium for monodisperse spherical particles

Abstract: A system of identical particles interacting through an isotropic potential that allows for two preferred interparticle distances is numerically studied. When the parameters of the interaction potential are adequately chosen, the system exhibits coexistence between two different liquid phases (in addition to the usual liquid-gas coexistence). It is shown that this coexistence can occur at equilibrium, namely, in the region where the liquid is thermodynamically stable.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 18 publications
5
117
0
1
Order By: Relevance
“…Two of the models (the TIP5P [45] and the ST2 [46]) treat water as a multiple site rigid body, interacting via electrostatic site-site interactions complemented by a Lennard-Jones potential. The third model is the spherical ''two-scale'' Jagla potential with attractive and repulsive ramps which has been studied in the context of liquid-liquid phase transitions and liquid anomalies [21,[30][31][32]47,48]. For all three models, Xu et al evaluated the loci of maxima of the relevant response functions, compressibility and specific heat, which coincide close to the critical point and give rise to the Widom line.…”
Section: Results For Bulk Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the models (the TIP5P [45] and the ST2 [46]) treat water as a multiple site rigid body, interacting via electrostatic site-site interactions complemented by a Lennard-Jones potential. The third model is the spherical ''two-scale'' Jagla potential with attractive and repulsive ramps which has been studied in the context of liquid-liquid phase transitions and liquid anomalies [21,[30][31][32]47,48]. For all three models, Xu et al evaluated the loci of maxima of the relevant response functions, compressibility and specific heat, which coincide close to the critical point and give rise to the Widom line.…”
Section: Results For Bulk Watermentioning
confidence: 99%
“…Unlike other network forming materials [26], water behaves as a non-Arrhenius liquid in the experimentally accessible window [16,27,28]. Based on analogies with other network forming liquids and with the thermodynamic properties of the amorphous forms of water, it has been suggested that, at ambient pressure, liquid water should show a dynamic crossover from non-Arrhenius behavior at high T to Arrhenius behavior at low T [24,[29][30][31][32][33]. Using Adam-Gibbs theory [34], the dynamic crossover in water was related to the C max P line [22,35].…”
Section: The Widom Linementioning
confidence: 99%
“…[32][33][34][35][36] In addition, the possibility of a LLPT has been seen in computer simulations of many other pure fluids. [37][38][39][40][41][42][43][44] More importantly, technical questions regarding equilibration raised in Refs. 30 and 31, have no bearing on the qualitative transformations of the glassy states we examine, which are inherently nonequilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments as well as simulations suggest that the anomalous thermodynamic and kinetic properties of water are due to the fluctuating, three-dimensional, locally tetrahedral hydrogen-bonded network. Water-like anomalies are seen in other tetrahedral network-forming liquids, such as silica, as well as in model liquids with isotropic core-softened or two-scale pair potentials [3,4,5,6,7,8,9,10,11].In the case of liquids such as water and silica, a quantitative connection between the structure of the tetrahedral network and the macroscopic density or temperature variables can be made by introducing order metrics to gauge the type as well as the extent of structural order [6,7]. The local tetrahedral order parameter, q tet , associated with an atom i (e.g.…”
mentioning
confidence: 99%